No effect of serum electrolyte levels on electroconvulsive therapy seizure quality parameters - Karl, Sebastian; Sartorius, Alexander; Aksay, Suna Su (The journal of ECT, 2024)
Introduction - Seizure quality is considered to be associated with treatment outcomes of electroconvulsive therapy (ECT). A wide range of treatment parameters and patient characteristics are known to influence seizure quality. However, conflicting results exist for the role of serum electrolyte levels and seizure quality. - Methods - We retrospectively analyzed a total of 454 patients and a total of 2119 individual acute ECT sessions irrespective of diagnosis where a clinical evaluation of serum levels of sodium, potassium, and calcium took place routinely up to 2 days before the ECT session. To assess the impact of serum electrolyte levels on seizure quality parameters, we used mixed-effects linear regression analysis with Bonferroni correction for multiple testing. - Results - Serum sodium, potassium, and calcium levels were not associated with seizure quality markers after correcting the significance level for multiple testing. Younger age was consistently associated with higher postictal suppression, interhemispheric coherence, midictal amplitude, and peak heart rate. Lower dose was consistently associated with longer electroencephalogram and motor seizure duration. - Conclusions - Our results suggest that there is no clinically relevant effect of serum electrolyte levels on seizure quality, at least within clinically commonly observed ranges of serum electrolyte concentrations.